Using Innovative Technologies in the Process of Teaching Maritime English - Ariana Oktavia; Dhanan Abimanto (International Journal of Educational Development, 2024)
This study explains the using innovative technologies in the process of teaching maritime English. English is always important in Maritime, especially in using innovative technologies such as: robotic technology, Artificial Intelligence (AI), networked sensors, advanced monitoring system, and blockchain technology. In teaching Maritime English, the maritime sector needs English as a language in communication medium to promote understanding between the teachers and students. The Maritime Communication Program helps maritime industry professionals to communicate better in English and across cultures. Through a research approach qualitative descriptive, to get the innovative technologies in teaching Maritime English. By using the theory of Standards of Training, Certification and Watchkeeping for Seafarers (STCW). The results in this study are developed business English course for the shipping industry and other maritime sectors, help professionals with different nationalities and cultural backgrounds communicate effectively and with ease. This is imminent for safety reasons, but it also supports companies that employ people from all over the world maintain main quality standards in a very dynamic and competitive environment.